Understanding cultural and social influences on female entrepreneurship in Mandan village, China - Qu, Mingjing (Journal of Community Positive Practices, 2024)
This qualitative study delves into the intricate interplay of cultural norms, social networks, and unique challenges impacting female entrepreneurship in Mandan Village, Yunnan Province, China. Amidst evolving economic realities and entrenched traditional values, this research aims to unravel how these factors shape women’s entrepreneurial endeavors in a rural context. The study’s objectives are threefold: (1) to explore the influence of cultural norms on female entrepreneurship, (2) to investigate the role of social networks in supporting or challenging female entrepreneur, and (3) to identify the unique challenges and opportunities faced by female entrepreneurs in Mandan Village. Employing semi-structured interviews, field observations, and analysis of government documents, the study captures diverse perspectives from 3 village committee members, 6 local residents, 3 NGO representatives, and 3 female entrepreneurs, totaling is 15 individuals. Results uncover that conventional social standards altogether impact ladies’ choices to become entrepreneurs and the kinds of organizations they lay out. Social networks are found to assume an essential part, offering fluctuating levels of assistance and assets. Female entrepreneurs face difficulties like adjusting business and family obligations, restricted admittance to resources, and exploring the digital gap. These experiences add to a nuanced comprehension of the variables influencing rural female entrepreneurship, offering important ramifications for policymakers, educators, and local area leaders. This research enriches the academic discourse on gender, culture, and entrepreneurship and underscores the importance of considering local contexts in fostering female economic empowerment and entrepreneurial choices in rural settings.